Genotypic diversity of Dictyosphaerium–morphospecies (Chlorellaceae, Trebouxiophyceae) in African inland waters, including the description of four new genera - Krienitz, L.; Bock, Christina; Kotut, Kiplagat; Pröschold, Thomas (My University, 2012)
Trebouxiophytes of the Dictyosphaerium–morphotype from inland waters of Africa were studied using a polyphasic approach of SSU and ITS rDNA phylogeny, secondary structure of the ITS and observations made with a light microscope. Although the morphological criteria for differentiating species and genera are scarce, the genetic diversity of these algae was very high. Based on our genetic analysis findings, we described four new genera containing five new species: Compactochlorella dohrmannii, Compactochlorella kochii, Kalenjinia gelatinosa, Marasphaerium gattermannii and Masaia oloidia. Diversity and distribution of Chlorella–related colonial chlorophytes in the tropical and temperate zones were compared and discussed.
Keywords: Inland waters of Africa; Chlorella; Compactochlorella nov. gen.; Dictyosphaerium; diversity; geographic distribution; green algae; Kalenjinia nov. gen.; Marasphaerium nov. gen.; Masaia nov. gen.